Reduce Fuel Consumption in Poultry Houses by Leveraging Day-Night Temperature Variations in the MENA Region. (مجلة العلوم الشاملة, 2025)
This paper presents the development of an algorithm aimed at reducing fuel consumption in poultry houses, specifically designed to leverage the significant differences in day and night temperatures in the MENA region during winter. This algorithm is a key component of a comprehensive Poultry House Management System (PHMS). The proposed algorithm adjusts heating and ventilation parameters based on real-time environmental data and bird activity levels. By exploiting natural temperature fluctuations, dynamically allowing more fresh air into the house during warm time of the day and reducing it to a minimum during cold time during the night, the algorithm demonstrated a substantial reduction in fuel usage—up to 30%—without compromising the health and productivity of the poultry, contributing to the overall efficiency of the PHMS. Additionally, increased fresh air intake helps dry litter pads and remove moisture, further enhancing the poultry house environment.